INTRODUCTION TO ELECTRICAL ENGINEERING: SEMICONDUCTOR ENERGY BAND CONCEPTS - Mardiki Supriadi (Adisam Publisher, 2025)
Introduction to Electrical Engineering covers various fundamental concepts, one of which is the concept of energy bands in semiconductors. Understanding this concept is very important because semiconductors are the basic materials in many electronic devices, including transistors, diodes, and integrated circuits. The energy band theory provides important insights into the electrical properties and conductivity of solid materials. By understanding this concept, it can be explained why some materials are conductors, insulators, or semiconductors. The energy band theory is very important in the development and understanding many different electronic components, including solar cells, LEDs, diodes, and transistors. Understanding the electrical and optical properties of semiconductor materials requires an understanding of the energy band. There are two primary components to the energy band: the band of valence and the conduction band. The valence band is an energy band that may be filled by electrons from a solid to a complete state, while the conduction band is an energy band above the valence band that may be filled by electrons that have higher energy. The concept of energy bands is one of the important concepts in understanding the properties of semiconductors. The energy band is the range of energy available to electrons in a material. Semiconductors have many applications in the field of electronics. For example, semiconductors are used in the manufacture of computers, electronic devices, thermocouples, and many more.